Physical activity and maximal aerobic capacity in breast cancer survivors: Why this is important - Brdareski Zorica; Đurović Aleksandar; Šušnjar Snežana; Životić-Vanović Mirjana; Ristić Anđelka; Konstantinović Ljubica; Vučković-Dekić Ljiljana; Tankosić Mirjana (Vojnosanitetski Pregled, 2014)
nema